ANEKA PRODUK OLAHAN BUAH NENAS SEBAGAI ALTERNATIF PENINGKATAN NILAI TAMBAH PRODUK DI DESA GALANG, KABUPATEN MEMPAWAH - Indrawati, Urai Suci Yulies Vitri; Hazriani, Rini (Jurnal Dinamika Pengabdian, 2020)
The application of PKM aims to empower organic pineapple farmers (Galang UKM) in an effort to innovate pineapple-based product diversification, so that people can get to know a variety of pineapple products (pineapple syrup) and know the benefits of consuming pineapple syrup in which marketing is still quite extensive, especially for the region outside Mempawah Regency. In addition, participants were given attractive labeling and packaging design technology, good and correct bookkeeping training in recording the benefits of marketing this syrup. In its activities, the lecturer team was assisted by 3 students. Activities in this service include the manufacture of hygienic pineapple syrup. Designing more hygienic and attractive packaging typical of Galang UKM, Financial bookkeeping training for UKM and at the end of the activity, an evaluation of the programs carried out by the lecturer team, which aims to find out the obstacles / difficulties encountered during the activity process, and then discussed to be completed followed by an exhibition of finished product businesses. It is expected that after this activity is completed, UKM Galang is able to produce pineapple processed products (pineapple syrup) that have good quality and help the Food Security Program in West Kalimantan Province.   Keywords: Various processed, label design, pineapple, empowerment, pineapple syrup.   ABSTRAK Penerapan PKM ini bertujuan untuk  pemberdayaan masyarakat tani nenas organik (UKM Galang)  dalam upaya melakukan inovasi diversifikasi produk berbasis nenas , sehingga masyarakat dapat mengenal beraneka produk nenas (sirup nenas) dan mengetahui manfaat apabila mengkonsumsi sirup nenas yang mana pemasarannya masih cukup luas terutama untuk wilayah di luar Kabupaten Mempawah. Selain itu kepada peserta di berikan teknologi mendesign label dan kemasan yang menarik, pelatihan pembukuan yang baik dan benar dalam mencatat keuntungan dari pemasaran sirup ini. Dalam kegiatannya, tim dosen dibantu oleh 3 orang mahasiswa. Kegiatan dalam pengabdian ini  yaitu pembuatan sirup nenas yang hygienis,. Mendesign  kemasan yang lebih hygienis dan menarik khas UKM Galang, Pelatihan pembukuan finansial kepada UKM dan pada akhir kegiatan, dilakukan evaluasi terhadap program-program yang telah dilakukan oleh tim dosen, yang bertujuan untuk mengetahui hambatan/kesulitan yang dihadapi selama proses kegiatan, dan kemudian didiskusikan untuk diselesaikan dilanjutkan dengan pameran usaha produk yang telah jadi. Diharapkan setelah kegiatan ini selesai, UKM Galang  mampu menghasilkan produk olahan nenas (sirup nenas) yang mempunyai kualitas yang baik dan membantu Program Ketahanan Pangan di Provinsi Kalimantan Barat.   Kata kunci: Aneka olahan, disain label, nenas, pemberdayaan, sirup nenas.